The Use of Conceptual Metaphor in Gola Gong’s Novel Bila Waktu Bicara - Faizal Risdianto (UIN Salatiga, 2010)
This study aims at describing conceptual metaphor in Gola Gong’s novel “Bila Waktu Bicara” in the perspective of George Lakoff’s theories of metaphor. This research is a (qualitative) bibliographical research. The object of the study is the use of metaphor in Gola Gong’s novel “Bila Waktu Bicara” and there are 59 metaphorical expressions. Having analyzed the data, the researcher concludes that there are seven most outstanding conceptual mapping on that novel: time is an individual, the world is the hell or paradise, people is a stream of water, seeing is touching, eye ball is a container, body part is a landscape, ambulance is an individual. Among this seven conceptual mappings, the conceptual pattern of time is an individual is the most frequent use and it shows that there has been an increase of creativity in the creation of socio-religious metaphor of Indonesian young novelist such as Gola Gong. Keywords:Source Domain; Conceptual Metaphor; George Lakoff